Diary of a Wimpy Kid : Rodrick Rules - Book 2 - Kinney, Jeff (New York : Amulet Books, 2008)
Greg Heffley tells about his summer vacation and his attempts to steer clear of trouble when he returns to middle school and tries to keep his older brother Rodrick from telling everyone about Greg's most humiliating experience of the summer.
Accelerated Reader AR
A Junior Library Guild selection
Keywords: Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Families -- Juvenile fiction; Diaries -- Juvenile fiction; Children's stories